Progression and prognostic significance of electrocardiographic findings in patients with cardiac amyloidosis - Alessia Argirò; Mattia Zampieri; Carlotta Mazzoni; Carlo Fumagalli; Michela Baccini; Alessandra Mattei; Alberto Cipriani; Laura De Michieli; Aldostefano Porcari; Gianfranco Sinagra; Marco Merlo; Giacomo Tini; et al. (ESC Heart Failure)
Abstract Aims This study aimed to evaluate the change of the main electrocardiographic (ECG) characteristics and their prognostic role across the main subtypes of cardiac amyloidosis [light‐chain amyloidosis (AL) and hereditary (ATTRv) and wild‐type transthyretin amyloidosis (ATTRwt)]. Methods and results This multicentre, retrospective study was performed in six referral centres for cardiac amyloidosis. Clinical and ECG data were collected at the first and last evaluations. Three hundred fifty‐six patients were included (AL, n = 105; ATTRv, n = 50; ATTRwt, n = 201). The median age was 76 (67–81) years, and 271 (74%) were men. At baseline, patients with ATTRwt showed a higher prevalence of conduction abnormalities compared with those with AL [first‐degree atrioventricular block, n = 51 (40%) vs. n = 13 (34%), P < 0.01; left bundle branch block, n = 23 (11%) vs. n = 2 (2%), P < 0.01], and patients with AL more often had low QRS voltage [n = 58 (55%); in ATTRv, n = 17 (34%); in ATTRwt, n = 67 (33%), P value < 0.01] and T wave inversion compared with those with ATTR [n = 39 (37%); in ATTRv, n = 9 (18%); in ATTRwt, n = 37 (18%)]. After a median follow‐up of 15 (8–26) months, the adjusted differences in mean PR, QRS interval, total, peripheral, and precordial QRS scores were similar across subtypes of amyloidosis (P value for linear regression > 0.05). The adjusted odds ratios for the development of right bundle branch block were higher in AL compared with ATTRwt [odds ratio 4.7 (95% confidence interval 1.5–15), P < 0.05]. QRS duration at baseline remained independently associated with patient survival in the overall population even after adjustment for relevant clinical variables [hazard ratio 1.78 (95% confidence interval 1.13–2.8), P < 0.01]. Conclusions The progression of the ECG abnormalities seems similar across amyloidosis subtypes. QRS duration could be a marker of more advanced disease.